From the New Editor. (April 2016) - Fraser, John
Abstract: With the passage of ownership of Curator: The Museum Journal from the California Academy of Sciences (CAS) to John Wiley and Sons, Inc., John Fraser has been appointed as the new Editor. His article summarizes the circulation growth of the journal since Wiley first began publishing the title. The expansion is visible in the number of libraries, the global distribution, and access at low or no cost to institutions in developing economies of the journal. The new editor envisions further growth, and plans a vibrant social media presence, enlarged editorial board, and a continuation of his predecessor's legacy.